Hubungan Modifikasi Gaya Hidup dengan Kualitas Hidup Pasien Hipertensi di UPTD PKM Adan Adan Gurah Kediri - Nurul Laili; Vela Purnamasari (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2019)
Hypertension is a major contributor to vascular diseases such as stroke, myocardial infarction, chronic kidney disease and congestive heart failure. Hypertension causes a significant increase in medical costs and decreased productivity. Health conditions that decline in a long period of time will affect the quality of life for all life activities of hypertensive patients. The aim of the study was to identify the relationship between lifestyle modification and quality of life in hypertensive patients. The design used was cross sectional.The population in this study were all patients who had hypertension. The sampling technique used was purposive sampling.The sample in this study were hypertensive patients who were controlled at UPTD PKM Adan-Adan Gurah Kediri in May-June 2019 as many as 69 respondents. The instrument use of a questionnaire from evidence-based related lifestyle modifications and WHO QoL-BREF Instruments for quality of life.The analysis was carried out in this study by using the Spearman Rank Correlation. Spearman Rank Correlation Test results obtained values ​​from Rho = 0.60 which indicates a strong level of relationship. The statistical test value t = 5.27 is greater than the value of t table = 2,000, then H₁ is accepted, meaning that there is a relationship between lifestyle modification and the quality of life of Hypertensive patients at UPTD PKM Adan-Adan Gurah Kediri. The quality of life with hypertension needs to be considered since the patient is diagnosed. The impact of hypertension results in physical and psychological changes discomfort, anxiety and depression that affect their activities. The main purpose of managing hypertension is to reduce the risk of complications and improve quality of life through improved health function, minimizing physical, psychological complaints and developing social functions. Management includes weight control (diet), exercise, salt restriction and stress management. Efforts to overcome the problem of hypertension include 3 main components, surveillance, promotion and prevention and management of hypertension services. Strategies that help officers and the public to know as early as possible the tendency of hypertension, so that it can reduce morbidity and mortality.